Governance in the Post‐Soviet Era: Challenges and Opportunities. (17th December 2018) - Baimenov, Alikhan; Liebert, Saltanat
Abstract: In the aftermath of the Soviet Union's demise, the countries formerly comprising it embarked on massive reforms to transition from socialist to market‐driven economies. This transition also required substantial transformation of their governance systems. In this Viewpoint essay, the authors reflect on critical reforms in human resource management, ethics management, and anti‐corruption, and highlight successful initiatives in these fields. They also discuss the role of the Astana Civil Service Hub in helping the countries in the region to jointly look for solutions to common governance challenges and to learn from policies and strategies that proved effective for their peers. The authors conclude by identifying the common elements of effective public administration reforms in the post‐Soviet setting.